Pemaknaan Saksi dan Keterangan Saksi dalam Teks Hukum - Frans Sayogie (Buletin Al-Turas, 2017)
AbstractMeanings of words and phrases in  legal text often lead a debate in the legal sphere. The ambiguity of the legal text would lead to uncertainty, injustice and inexpediency of law, because law is tied to language that basically always will give the interpretation of a written text of law. As a result of not fulfilled the terms of the law in the form of a written text of law like clarity,  unambiguity, conciseness, and inclusion, meanings of words and phrases in  legal text often, in this case, are often reviewed  in  The Constitutional Court of Republic of Indonesia. The Constitutional Court of Republic of Indonesia’s Decision No. 65 / PUU-VIII / 2010 reviewed the meaning of word witness  and phrase  witness statements is analyzed by semantic and syntactic approach which aim  to find alternative and comprehensive answers in the meaning of word witness  and phrase  witness statements.---AbstrakPemaknaan kata dan frasa dalam teks hukum sering menjadi perdebatan dalam ranah hukum. Ambiguitas teks hukum akan menimbulkan ketidakpastian, ketidakkeadilan, dan ketidakkemanfaatan hukum, dikarenakan  hukum terikat pada bahasa yang  pada dasarnya selalu akan memberikan penafsiran dari teks tertulis di dalam peraturan perundang-undangan. Akibat tidak dipenuhi syarat-syarat dalam teks hukum yang berupa kejelasan (clarity), ketidaktaksaan (unambiguity), bernas (concise), dan inklusif  sering dilakukan pengujian pemaknaan dalam teks hukum, dalam hal ini, di Mahkamah Konstitusi. Putusan Mahkamah Konstitusi Nomor 65/PUU-VIII/2010 yang menguji pemaknaan kata  “saksi” dan frasa “keterangan” saksi dianalisis dengan pendekatan semantis dan sintaksis, yang bertujuan untuk mencari jawaban alternatif dan komprehensif dalam pemaknaan kata “saksi” dan frasa “keterangan saksi”.DOI: 10.15408/al-turas.v23i1.4804